Kontroversi Tafsir Ilmi Dalam Penafsiran: Antara I’jaz Ilmiah dan Dakhil Penafsiran - Muhammad Arif; Dwi Sukmanila Sayska; Irhas (ISME : Journal of Islamic Studies and Multidisciplinary Research, 2026)
Scientific Interpretation is a Qur’anic interpretive approach that employs scientific knowledge to explain verses related to natural phenomena (ayat-ayat kauniyah). Its emergence has generated considerable debate among Muslim scholars. Some regard it as a manifestation of the Qur’an’s scientific miraculousness (i‘jaz ‘ilmi), demonstrating the harmony between revelation and scientific advancement, while others consider it a form of extraneous interpretation (Dakhil fi al-tafsir) that imposes modern scientific theories upon the Qur’anic text. This article aims to examine the position of scientific Interpretation within the Islamic Interpretation tradition by analyzing the arguments of both its proponents and critics. The study employs a qualitative library research method through a critical review of classical and contemporary scholarly works. The findings indicate that supporters of scientific Interpretation view it as a means of demonstrating the miraculous nature of the Qur’an, reconciling religion and science, and strengthening faith. In contrast, its critics argue that it may lead to interpretations that depart from the apparent meaning of the text, neglect contextual considerations, and tie Qur’anic meanings to scientific theories that are inherently tentative and subject to change. This study concludes that scientific Interpretation can be accepted when applied proportionally, without forcing scientific meanings onto the text, while remaining consistent with established principles of Arabic linguistics and Qur’anic interpretation, and relying only on well-established scientific facts. Under these conditions, scientific Interpretation may enrich the understanding of Qur’anic cosmological verses without undermining the primary function of the Qur’an as divine guidance.